1995
DOI: 10.1111/j.1600-0749.1995.tb00673.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pinkeyed‐Dilution Protein and the Eumelanin/Pheomelanin Switch: In Support of a Unifying Hypothesis

Abstract: The two major types of mammalian melanin are pheomelanin (yellow or red pigment) and eumelanin (black or brown). The agouti (A) and extension (E) loci determine whether follicular melanocytes will deposit pheomelanin or eumelanin within their melanosomes. Mutations at the murine pinkeyed-dilution (P) locus cause a striking reduction in deposition of eumelanic, but not pheomelanic, pigment. The mRNA encoded at the P locus is not expressed in skin that exclusively produces pheomelanic pigment as a result of muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 73 publications
(76 reference statements)
2
45
0
Order By: Relevance
“…Transient expression of ASP from days 4-6 of the hair growth cycle switches follicular melanocytes to the production of pheomelanin rather than eumelanin; after that, agouti gene expression is turned off, and eumelanin is produced again. Analyses of protein and mRNA expression during such hair growth have shown that tyrosinase-related protein (TRP) 1, TRP2, Pmel17͞silver, and the protein encoded at the pinkeyed-dilution locus are completely suppressed during pheomelanogenesis, whereas expression of tyrosinase is reduced but not eliminated (9,10). This pattern of expression is consistent with the fact that tyrosinase is required for both types of pigment synthesis, but expression of these other melanogenic proteins is required only for eumelanin synthesis.…”
mentioning
confidence: 57%
“…Transient expression of ASP from days 4-6 of the hair growth cycle switches follicular melanocytes to the production of pheomelanin rather than eumelanin; after that, agouti gene expression is turned off, and eumelanin is produced again. Analyses of protein and mRNA expression during such hair growth have shown that tyrosinase-related protein (TRP) 1, TRP2, Pmel17͞silver, and the protein encoded at the pinkeyed-dilution locus are completely suppressed during pheomelanogenesis, whereas expression of tyrosinase is reduced but not eliminated (9,10). This pattern of expression is consistent with the fact that tyrosinase is required for both types of pigment synthesis, but expression of these other melanogenic proteins is required only for eumelanin synthesis.…”
mentioning
confidence: 57%
“…The obtained results confirmed the predominant role in eye colour inheritance of two genes located on chromosome 15; that is, HERC2 and OCA2. The OCA2 gene encodes a protein that is an integral part of the melanosomal membrane and is responsible for regulation of pH inside the melanosome, [55][56][57] which, in consequence, has an influence on the activity of the enzyme tyrosinase, which has a crucial role in the synthesis of the pigment melanin. The important role of OCA2 in eye colour determination was confirmed in many studies, 11,13,28,31,[58][59][60][61] and further investigations revealed that regulation of OCA2 expression through the neighbouring HERC2 gene might have a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrp1, Dct, and Pmel encode melanogenic genes and are well-known targets of Mc1r based on studies of cultured melanocytes (Kobayashi et al 1995;Lamoreux et al 1995), but an effect of Mc1r on Brca2 and Smug1 has not been described previously and may contribute to differences in skin cancer susceptibility. We also note that Slc7a11, which encodes a melanocyte-specific cystine transporter that is essential for pheomelanin (yellow pigment) synthesis (and in which a loss-of-function is responsible for the subtle gray coat color mutation), is up-regulated (19.2 TPM in Mc1r +/+ vs. 44.5 TPM in Mc1r e/e skin), which supports a hypothesis based on biochemical studies that cystine transport plays an instructive role in pigment-type switching (Chintala et al 2005;Simon et al 2009).…”
Section: Edge In a Model Organism: Technical Characteristicsmentioning
confidence: 99%
“…Studies of additional cheetah samples will a Expression levels are given as tags per million reads of an EDGE library prepared from RNA of a black spot or yellow background area of cheetah skin. The genes shown here were chosen based on their roles in pigment cell biology; six are well-established melanocyte transcriptional targets downstream from MC1R signaling (Kobayashi et al 1995;Lamoreux et al 1995;Chintala et al 2005;April and Barsh 2006;Le Pape et al 2009); four encode secreted factors that act upstream, either as ligands or to modify ligands of the MC1R Enshell-Seijffers et al 2008;Kaelin et al 2008); and one, MITF, encodes a transcription factor required for melanocyte development (Steingrímsson et al 2006). The expected direction, increase (+) or decrease (À), for expression level change of each gene is given according to when pigment production switches from yellow pheomelanin to black eumelanin.…”
Section: à4mentioning
confidence: 99%